Delirious consumption : aesthetics and consumer capitalism in Mexico and Brazil - Delgado Moya, Sergio (Border Hispanisms., 2017)
In the decades following World War II, the creation and expansion of massive domestic markets and relatively stable economies allowed for mass consumption on an unprecedented scale, giving rise to the consumer society that exists today. Many avant-garde artists explored the nexus between consumption and aesthetics, questioning how consumerism affects how we perceive the world, place ourselves in it, and make sense of it via perception and emotion. Delirious Consumption focuses on the two largest cultural economies in Latin America, Mexico and Brazil, and analyzes how their artists and writers both embraced and resisted the spirit of development and progress that defines the consumer moment in late capitalism. Sergio Delgado Moya looks specifically at the work of David Alfaro Siqueiros, the Brazilian concrete poets, Octavio Paz, and Lygia Clark to determine how each of them arrived at forms of aesthetic production balanced between high modernism and consumer culture. He finds in their works a provocative positioning vis-à-vis urban commodity capitalism, an ambivalent position that takes an assured but flexible stance against commodification, alienation, and the politics of domination and inequality that defines market economies. In Delgado Moya's view, these poets and artists appeal to uselessness, nonutility, and noncommunication-all markers of the aesthetic-while drawing on the terms proper to a world of consumption and consumer culture Book jacket.